THE EFFECT OF A COMBINATION AND FREKUENCY OF APPLICATION OF LIQUID ORGANIC FERTILIZER ON GROWT AND YIELD OF PURPLE EGGPLANT ON PEAT SOILS - Agung Jimantoro; Nurjani ,; Maulidi . (Jurnal Sains Pertanian Equator, 2020)
This study aims to determine the effect of a combination of concentration and frequency of application of liquid organic fertilizer on the growth and yield of purple eggplant on peat soils. The research was conducted in the experimental garden of Faculty of Agriculture, University of Tanjung pura Pontianak. The design used was a Completely Randomized Design (CRD) consisting of 6 treatments and 4 replications, each repetition consisted of 3 plant samples. The intended treatment is 2 ml/1 liter of water 3 days (P1), 4 ml/1 liter of water 3 days (P2), 6 ml/1 liter of water 3 days (P3), 3 ml/1 liter of water 7 once a day (P4), 4 ml/1 liter of water 7 days (P5), and 6 ml/1 liter of water 7 days (P6).The variables observed in this study include: plant height, number of fruits per plant, fruit weight per plant, length of fruit per crop, and diameter of fruit per plant. The results of the analysis of the diversity of various combinations and the frequency of POC administration gave no significant effect on the observation variables, plant height, number of fruits, and fruit length, but significantly affected the eggplant yield components in peat soils, namely the observation of fruit weight and fruit diameter. In this study found effective combinations of concentrations and frequencies for growth and yield of eggplant on peat that is 4 ml/l liter of water once every 7 days.  Keywords : concentration and frequency of POC, purple eggplant, peat